Urgensi Pendidikan Toleransi Berbasis Al-Quran dalam Membentuk Tunas Bangsa Perilaku Humanis - Lili Sholehuddin Badri (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2024)
AbstractÂ Horizontal conflict is a reincarnation of a latent movement in the form of intolerant attitudes that have actually resulted in dehumanisation and demoralisation of life among fellow elements of society with the occurrence of various forms of humanitarian crises. This research seeks to portray and formulate strategies for the formation of humanist national budding behaviour through a tolerance education approach based on verses of the Qur'an. The research design is qualitative, including the type of library research. Data processing uses content analysis, namely examining the verses of tolerance education chronologically according to the revelation of the verse, collected, grouped, and sorted out then drawn conclusions using the inductive method. The research findings show that tolerance education upholds the dignity of humanity, teaches the values of equality, recognition, harmony, equal rights and the paradigm of solving problems wisely, effectively and proportionally. Tolerance education based on the Qur'an can be believed to be an alternative strategy for preparing superior generations, dignity and integrity in realising the nation's children who behave religiously, egalitarian and humanist.